Patients' Experiences With Staphylococcus aureus and Gram-negative Bacterial Bloodstream Infections: A Qualitative Descriptive Study and Concept Elicitation Phase To Inform Measurement of Patient-reported Quality of Life. (23rd May 2020) - King, Heather A; Doernberg, Sarah B; Miller, Julie; Grover, Kiran; Oakes, Megan; Ruffin, Felicia; Gonzales, Sarah; Rader, Abigail; Neuss, Michael J; Bosworth, Hayden B; Sund, Zoë; Drennan, Caitlin; et al.
Abstract: Background: Although S taphylococcus aureus and gram-negative bacterial bloodstream infections (SAB/GNB) cause substantial morbidity, little is known regarding patient perceptions' of their impact on quality of life (QOL). Guidance for assessing QOL and disease-specific measures are lacking. We conducted a descriptive qualitative study to gain an in-depth understanding of patients' experiences with SAB/GNB and concept elicitation phase to inform a patient-reported QOL outcome measure. Methods: We conducted prospective one-time, in-depth, semi-structured, individual, qualitative telephone interviews 6– 8 weeks following bloodstream infection with either SAB or GNB. Patients were enrolled in an institutional registry (tertiary academic medical center) for SAB or GNB. Interviews were audio-recorded, transcribed, and coded. Directed content analysis identified a priori and emergent themes. Theme matrix techniques were used to facilitate analysis and presentation. Results: Interviews were completed with 30 patients with SAB and 31 patients with GNB. Most patients were at or near the end of intravenous antibiotic treatment when interviewed. We identified 3 primary high-level concepts: impact on QOL domains, time as a critical index, and sources of variability across patients. Across both types of bloodstream infection, the QOL domains most impacted were physical and functional, which was particularly evident among patients with SAB. Conclusions: SAB/GNB impact QOL among survivors. In particular, SAB had major impacts on multiple QOL domains. A combination of existing, generic measures that are purposefully selected and disease-specific items, if necessary, could best capture these impacts. Engaging patients as stakeholders and obtaining their feedback is crucial to conducting patient-centered clinical trials and providing patient-centered care. Abstract : SAB and GNB impact quality of life among survivors. Existing, generic measures that are purposefully selected and disease-specific items, if necessary, could best capture these impacts. Engaging patients as stakeholders is crucial to conducting patient-centered clinical trials and providing patient-centered care.